Sultan Murad IV’s Polish Campaign (1634) - Cevrioğlu, Mahmut Halef (Instytut Historii PAN, 2020)
The present study depicts the developments which took place at the Polish-Ottoman frontier and in the Ottoman imperial centre between 1633 and 1634, when a fullscale war between the Polish-Lithuanian Commonwealth and the Ottoman Empire was imminent. Even though the major episodes of the conflict have been highlighted from the Polish perspective several times before, it is hard to say the same regarding the Ottoman vantage point. Therefore, this paper tries to make use of major European embassy reports from the Ottoman capital, with cross-references to the Ottoman archival documentation of the period. In this way the paper aims to expound the escalation and resolution of the conflict from the Ottoman point of view and seeks to fill the gap left by the already-established Polish stances. It will also serve the purpose of attracting attention both to the Polish diplomatic presence in the Ottoman capital and to the Ottoman diplomatic activity with regard to the Polish-Lithuanian Commonwealth in the years specified.
s. 209-246
Keywords: historia dyplomatyczna; Murad IV (sułtan turecki; 1612-1640); stosunki polsko-tureckie 17 w.; Trzebiński, Aleksander (?-1644); Wojny polsko-tureckie [KABA]; Osmańskie, Imperium -- 1453-1683 [KABA]; Turcja -- stosunki zagraniczne -- Polska -- 17 w. [KABA]; Polska -- stosunki zagraniczne -- Turcja -- 17 w. [KABA]